Cerebral venous thrombosis in a child with inflammatory bowel disease: case report - Rohani, Pejman; Javadzadeh, Mohsen; Khalili, Mitra; Zojaji, Reyhaneh (Iranian Journal of Child Neurology, 2021)
Abstract inflammatory bowel disease (IBD) has both intestinal and extra intestinal manifestations. Inflammatory bowel disease (IBD) is a known risk factor for cerebral venous thrombosis (CVT) event in adult and children. The precise mechanism of thrombotic event is not known in patient with IBD. We report a case of ulcerative colitis with CVT during admission for acute relapse. 12 years old boy known case of ulcerative colitis since 12 months ago admitted in children hospital because of bloody diarrhea, recurrent colicky abdominal pain. At the third day of admission patient had severe headache. Level of consciousness has decreased gradually during 12 hours. Child has been aphasic later. One episode of tonic clonic seizure has happened 18 hours after the onset of headache. Neurologic examination showed right hemiparesis. Physical examinations including blood pressure and fundoscopy were unremarkable in last admission. Brain CT shows intraparanchymal hemorrhage in left temporal lobe with asymmetric increased density in left lateral sinus. The results of MRI has shown abnormal hyperintense signal in left lateral sinus in T1WI and T2WI that is compatible with thrombosis (loss of signal) in MRV. LMW heparin was administered according to consultation with hematologist and continued post discharge. Child condition has improved slowly and neurologic evaluation was normal after 3months. Cerebrovascular events, such as cerebral venous thrombosis (CVT) or cerebral arterial infarction (CAI), are rare extraintestinal manifestations of PIBD but probably the most common forms of thromboembolism in children. Probably, treatment of CVT with anticoagulants is the best way of management. A comprehensive study is essential to understand the choice, efficacy, duration, and primary and secondary prophylaxis protocol with anticoagulants.